BALAGWALAZU: The Town of Seven Cotton Trees (African Knowledges and the History Publication since the 1970s, 1988)
Young girls' graduate from Sande "School" in Balagwalazu Village, Lofa County, Liberia.
Keywords: Culture; History; Tradition